Salafi Tafsirs: Textualist and Authoritarian? - Izza Rohman (Qur'an and Hadith Academic Society, 2012)
This essay looks at some Salafi tafsirs to examine the extent to which their interpretation ignores or rejects both the socio-historical context of revelation and that of interpretation, and the extent to which their interpretation denies any possibility to understand differently. Taking the hijabs verses as a a case study, the author shows similarities and differences between the three tafsirs under scrutiny in terms of their “textualism” and “authoritarianism”